Mandibular Fracture and Dislocation in a Case Study from the Jewish Cemetery of Lucena (CÓRDOBA), in South Iberian Peninsula (8th–12th ad). (12th August 2011) - De Luca, S.; Viciano, J.; Irurita, J.; López‐Lázaro, S.; Cameriere, R.; Botella, D.
ABSTRACT The skeletal remains of an adult female have been exhumed in an 11th century tomb in the mediaeval Jewish cemetery of Ronda Sur, in the city of Lucena (Córdoba, Spain). Examination of the skull and mandible revealed evidences of bilateral condylar fracture and dislocation. Lesions were observed macroscopically and radiology was used as a complementary method of scrutiny, especially in cases of unclear observation. Irregular morphology of the condyles and coronoid processes, shallow glenoid fossa, altered and abnormal joint surfaces anterior to the glenoid fossa, and reduced height of both ascending rami were observed. Ante‐mortem tooth loss, slight wear of occlusal surface and asymmetrical occlusal deposit of dental calculus were found. Radiologically, degenerative changes in the condyles and reparative bone in both coronoid processes have been identified. Dislocation of the condyles and lack of adequate treatment probably led to disruption of masticatory patterns and related structures, such as muscle attachments, articular disc and ligaments. Bilateral remodelled fracture and the altered appearance of the joint structures could probably mean that the individual survived the injury by several years. This type of fracture could be the consequence of direct blow to the mental or submental region that was transmitted in a direction that raised the mandible, causing the condylar head to collide directly with the mandibular fossa. Very few mandibular fractures in ancient skulls have been described in Spain, and this case is the first example found in a Spanish archaeological skeletal assemblage. Copyright © 2011 John Wiley & Sons, Ltd.